IMPLEMENTASI MONTE CARLO TREE SEARCH PADA PERMAINAN KARTU “DAIFUGO” - Eunike Thirza Hanitya Christian; R. Gunawan Santoso; Erick Purwanto (Universitas Kristen Duta Wacana, 2015)
Daifugo is climbing card game that is originated from Japan. AI player of Daifugo card game can be implemented using Monte Carlo Tree Search to get optimal result from random simulation. Monte Carlo Tree Search has 4 step, selection, expansion, simulation and backpropagation that is executed until maximal loop is reached. Objective of using Monte Carlo Tree Search on AI player in Daifugo card game is to get move with high winning rate and to observe the effect of number of loop on the method to winning rate